EXPENSES AND YIELDS IN MILKFISH BRACKISHWATER POND CULTIVATION A Descriptive Account of Tambak Cultivators and their Households in “Sumbersari” - Nurdien H Kistanto (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Methods of milkfish brackishwater pond cultivation consist of fry pond (for fry to fingerling rearing), milkfish brackishwater pond type 1 (designed for the cultivation of milkfish fingerlings to adult size) and milkfish brackishwater pond type 2 (for the cultivation of fry to adult or marketable size milkfish). Milkfish brackishwater pond cultivation is profitable, especially when the cultivation unit is larger. This account of milkfish brackishwater pond cultivators describes the details of expenses and yields of cultivating milkfish brackishwater pond as practiced by 4 (four) cultivators in “Sumbersari,” a coastal village in north Central Java.